Analisis Break Even Point (BEP) Dalam Menentukan Perencanaan Laba Perusahaan PT Sentra Food Indonesia 2021 - Aji Bimayu, Diemas (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Every company has a goal to gain profit or profit. Planning to estimate profits can be done with Break Even Point (BEP) analysis. The purpose of this study is to determine the company's Break Even Point and the company's safety margin at PT. Indonesian Food Center. This study uses secondary data with the Break Even Point analysis method. The results showed that the company did not gain or lose at a sales level of Rp. 88,394,979,725.-. Determination of sales targets using the break even point method in 2022 the company PT. Sentra Food Indonesia must sell products of Rp. 97,256,191,970, - to get a profit of Rp3,500,000,000, -. company margin of safety PT. Sentra Food Indonesia in 2021 obtains a safety margin level of 73% or the maximum amount of reduced sales revenue target so that the company does not experience a maximum loss situation of IDR 69,609,842,752.-.